Indicações geográficas e marcas coletivas: um olhar à região do Vale dos Vinhedos e da Vinhateiros do Vale - Rodrigues, Fernanda (2021)
Industrial property aims at the economic and technological development of the country. In its list of rights, there are distinctive signs of quality and origin of a product or service due to its geographical origin, as well as distinctive signs capable of distinguishing products and services from similar ones offered in the market. The first deals with geographical indications, the second deals with brands. The Brazilian legislation took care to protect such rights under the Federal Constitution of 1988 and through ordinary legislation, citing the Industrial Property Law - No. 9,279/96. Geographical indications aim to maintain the quality and origin of a given product or service that has characteristics originating from the geographical environment in which it is produced, acting in the protection of the cultural identity of the region. Brands serve to identify products and services placed on the market, differentiating them from similar products and services. Collective marks have the same power and can be used by members of the collective body that owns the institution. Thus, from an analysis of the geographical indication Vale dos Vinhedos and the collective brand Vinhateiros do Vale, the research questions: to what extent these two institutes, although different, complement each other and in what way the collective brand can be protagonist in the empowerment and development of small and medium wine producers? The objective is to analyze the similarities and differences of geographical indications and collective brands, verifying how they can complement each other and investigating the importance of the collective brand, especially for small and medium-sized producers, from the multidimensions of sustainability and the analysis of the Vale region. dos Vineyards and Vinhateiros do Vale. This study will be made possible by the systemic-complex theory of Fritjof Capra and Edgar Morin, using the deductive approach method and the methods of monographic procedure and indirect documentation. As for research techniques, abstracts and records will be used. It was concluded, therefore, that the link between geographical indications and collective brands can have an effect on the reach of the multidimensions of sustainability, as well as it was obtained that collective brands can consist of important protagonists of empowerment and reach of new markets to the small and medium wine producers.